Aquaculture over-optimism? - Sumaila, U. Rashid; Pierruci, Andrea; Oyinlola, Muhammed A.; Cannas, Rita; Froese, Rainer; Glaser, Sarah; Jacquet, Jennifer; Kaiser, Brooks A.; Issifu, Ibrahim; Micheli, Fiorenza; Naylor, Rosamond; Pauly, Daniel (Frontiers in Marine Science, 2022)
The recent rapid growth in aquaculture production reported by the United Nations Food and Agriculture Organization may have inadvertently generated what we denote here as aquaculture over-optimism. An extreme form of this is the notion that we need not worry about sustaining wild fish stocks because we can meet the global need through farming. Here we investigate whether the recent growth in aquaculture production can be maintained, and we compare aquaculture production projections with the future need for fish to find out whether aquaculture over-optimism can be justified. We show relevant evidences suggesting that aquaculture growth rates in all the cases studied have already reached their peak and have begun declining. Also, our results indicate that without wild fish, the world will face a fish food shortage of about 71 million tonnes annually by 2030, and the aquaculture production growth rate would have to be 3 times current average projected production by the FAO, the World Bank and the OECD in 2030. Finally, the current geographical distribution of farmed fish production suggests that even if aquaculture over-optimism is physically, economically, technically and ecologically feasible, its socio-economic cost to low-income coastal countries could be devastating.